Arithmetic and logic in computer systems - Lu, Mi (Wiley series in microwave and optical engineering, 2005)
The book describes the fundamental principles of computer arithmetic. Algorithms for performing operations like addition, subtraction, multiplication and division in digit computer systems are presented, with the goal of explaining the concepts behind the algorithms, rather than addressing any direct applications.